Detection of molecular markers associated with yield and yield components in durum wheat (Triticum turgidum L. var. durum) under saline conditions. Markers for yield in durum wheat - Dura S.; Duwayri M.; Nachit M.M. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Durum wheat is one of the most important staple food crops grown mainly in the Mediterranean region where its productivity is drastically affected by salinity. The study objectives were to identify markers associated with grain yield and its related traits under saline conditions. A population of 114 F8 recombinant inbred lines (RILs) was derived by single-seed descent from a cross between Belikh2 (salinity tolerant variety) and Omrabi5 (less salinity tolerant) was grown under non-saline and saline conditions in a glasshouse. Phenotypic data of the RILs and parental lines were measured for fifteen agronomic traits. Association of 48 SSR loci covering all 14 chromosomes with fifteen agronomic traits was analyzed with a mixed linear model. A total of 28 SSR loci were significantly associated with these traits. Under saline condition, 13 markers were associated with phenological traits while 19 markers were associated with yield and yield components. Marker alleles from Belikh2 were associated with a positive effect for the majority of markers associated with yield and yield components. Under saline condition, four markers (Xwmc182, Xwmc388, Xwmc398, and Xbarc61) were closely linked with grain yield, located on 3A, 3B, 4B, 5A, 6B, and 7A. These markers could be used for marker-assisted selection in durum wheat breeding under saline conditions.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)